'Orientalism is a Partisan Book': Applying Edward Said's Insights to Early Modern Travel Writing. Issue 4 (April 2016) - Roddan, Hector
Abstract: Since its publication in 1978, Edward Said's Orientalism has had a significant impact on postcolonial studies in a range of fields. This paper assesses his impact on the historiography of Anglophone travel writing concerning Ottoman Empire during the early modern period. Said's analysis of the relationship between representational power and colonial authority remains relevant to our understanding of early modern travel texts. Said's epistemology raises significant issues for historians of early modern intercultural encounters. This article summarises recent debates surrounding early modern travel narratives. It contrasts doctrinaire applications of Said's theory with more recent, particularistic studies. It provides a much‐needed survey of travel writing historiography that considers the continuing impact of Said's postcolonial thought on the study of early modern travel narratives relating to the Ottoman Middle East. In so doing, it explores the lack of fit between early modern travel narratives and Said's methodology. I explore the methodological problems thrown up by conventional applications of Said's epistemology to precolonial travellers' texts. Based on a wide‐ranging survey of Said's oeuvre, the article demonstrates that, more than 30 years on, Said's work remains relevant to the historiographical challenges presented by early modern English travel writing about Islam.